Thickness dependence of degree of B2 order of polycrystalline Co2(Mn0.6Fe0.4)Ge Heusler alloy films measured by anomalous X-ray diffraction and its impacts on current-perpendicular-to-plane giant magnetoresistance properties. (December 2020) - Nakatani, Tomoya; Narayananellore, Sai Krishna; Kumara, Loku Singgappulige Rosantha; Tajiri, Hiroo; Sakuraba, Yuya; Hono, Kazuhiro
Abstract: We investigated the degree of B2 order ( S B2 ) of 4-10 nm-thick polycrystalline Co2 (Mn0.6 Fe0.4 )Ge (CMFG) Heusler alloy films using anomalous X-ray diffraction (AXRD) and its correlation to the magnitude of current-perpendicular-to-plane giant magnetoresistive (CPP-GMR) effect. We found that S B2 of the CMFG films is degraded for the film thickness below 6 nm, which is an issue for practical applications of CPP-GMR devices such as read head sensors of hard disk drives. Since S B2 has a thickness-dependence, the bulk spin polarization ( β ) of the CMFG layers is also expected to vary depending on the thickness; thus, the deduction of β using the Valet-Fert model, where β is assumed to be thickness-independent, is not valid for these CPP-GMR devices. Graphical abstract: Image, graphical abstract